Benign Migratory Glossitis and Hand–Foot Syndrome Co-occurrence in a Renal Cell Carcinoma Patient on Sorafenib - Ramamoorthy Logamoorthy; Ragul Raj Elango; Shruti Ganesh; Suganya Radhakrishnan; Kaliaperumal Karthikeyan (Clinical Dermatology Review)
Sorafenib, a multitargeted tyrosine kinase inhibitor, is used for advanced renal cell carcinoma but can cause various cutaneous side effects. We report the case of a 50-year-old male with metastatic renal cell carcinoma who developed both benign migratory glossitis (BMG) and hand–foot syndrome (HFS) during sorafenib therapy. The patient, on sorafenib 200 mg twice daily, experienced painful fluid-filled lesions on his palms and soles and migratory hyperkeratotic lesions on his tongue. Diagnosis confirmed both HFS and BMG as side effects of sorafenib. Despite these issues, sorafenib remains essential for his treatment. Management included potent topical steroids and symptomatic relief strategies. This case underscores the need for recognizing and managing sorafenib-induced dermatological manifestations and highlights the importance of multidisciplinary care to balance treatment efficacy with quality of life.